Persepsi Wali Murid Madrasah Ibtidaiyah Nurul Huda 2 Kota Mojokerto dalam Penggunaan Google Classroom pada Pembelajaran Qur'an Hadits di Tengah Pandemi Covid 19 - Lailatul Badriyah; Husniyatus Salamah Zainyati (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2020)
This study aims to find out information on the perception of guardians of MI Nurul Huda 2 students in Mojokerto City in the use of Google classroom in learning the Qur'an Hadith in the middle of the Covid pandemic 19. The research uses an exploratory case study with a qualitative method approach to obtain information on student perception of guardians in the use of Google classroom on learning Qur'anic Hadith. In this study, there were 29 guardians of students in class 2 MI Nurul Huda 2 Mojokerto City. The instrument used was a questionnaire sent via online and interviews. The results showed that the guardians' perceptions of students regarding the use of Google classroom in learning the Qur'an Hadith were all stated to be an average of 60% of the socialization, planning and use, delivery of material and assessment of questions. And there are shortcomings namely the difficulty of the signal, spend internet pulses and alternately use cell phones at home. While the advantages can be seen directly in value after being corrected by the teacher, easier to use and understand the problem, and can increase knowledge in the development of technology learning.